Die Ruine als Fetisch - Stackmann, Sophie (MDCCC 1800)
This article is based on the theory that John Ruskin (1819‑1900) attributed a male gaze to decaying architecture in his writings and described it with feminine characteristics. Decaying architecture symbolizes ideal virginity, which can only be destroyed by a falsifying restoration. This reading of Ruskin’s writings will be linked to a critical history of architecture that examines architecture in its patriarchal normativity. Building on this link, a feminist reading of the history of monument conservation will be formulated.